2020
DOI: 10.1177/0261429420946858
|View full text |Cite
|
Sign up to set email alerts
|

IGNITE: Empowering high ability underachieving students to become focused learners in mainstream classes

Abstract: IGNITE, a high school-based programme, was developed for high ability underachievers using the Achievement Orientation Model (AOM), Maker Model, and Bibliotherapy in a mainstream setting. This paper reports on the effects discovered while implementing the programme over the course of 2 years. Year 7 (13 year olds) and Year 9 (15 year olds) students were trained to use the two interventions, incorporating one of these interventions to challenge their learning in the classroom. The programme for each cohort last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…While a range of studies focused on technology-assisted empowered learning [21]- [24], a number of studies had their focus on socially empowered learning [25]- [28]. Fewer studies targeted cognitive empowerment of students [29]- [31], whereas the remaining studies were spread across empowered learning in relation to psychological education [32], [33], sports education [34], [35], and health education [36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While a range of studies focused on technology-assisted empowered learning [21]- [24], a number of studies had their focus on socially empowered learning [25]- [28]. Fewer studies targeted cognitive empowerment of students [29]- [31], whereas the remaining studies were spread across empowered learning in relation to psychological education [32], [33], sports education [34], [35], and health education [36].…”
Section: Resultsmentioning
confidence: 99%
“…Self-regulated empowerment can be achieved by a number of steps taken by a learner to accept ownership of one's learning by vigorously engaging in learning to overcoming problem. Self-regulation and motivation act together to promote learners' empowerment where learners seek social support and acceptance of peers during the course of their learning [32].…”
Section: How Is Empowered Learning Conceptualized Within the Literatu...mentioning
confidence: 99%
“…There are several interventions that can help meet high school gifted students’ social and emotional needs, such as gifted enrichment programming, specific curricula, bibliotherapy, mentoring, collaboration, counseling, mindfulness, and therapy (Fisher & Kennedy, 2016; Kim, 2016; Long & Erwin, 2020; McDaniel & Besnoy, 2019; Olton-Weber et al, 2020; VanTassel-Baska et al, 2008; Woo et al, 2017). For example, Kim (2016) conducted a meta-analysis of 26 studies about the effects of gifted enrichment programming on gifted students’ and found it had a positive impact on gifted students’ social and emotional development (e.g., positive attitude toward school; improved academic and emotional self-concept).…”
Section: Background Literaturementioning
confidence: 99%